Pete the Cat and the Wright Brothers - Dean, Kim, 1969-; Dean, James, 1957- ([New York] : Harpercollins Childrens Books, 2024)
Pete the Cat helps the Wright brothers build their first flying machine in this historical fiction Level 1 I Can Read from New York Times bestselling creators Kimberly and James Dean. When Pete the Cat learns that the Wright brothers' flying machine can$1 (Bt fly without the wind, he has an idea. What if it didn$1 (Bt need wind to fly? Together, the cats invent the perfect solution. Pete may even get the chance to fly! This early reader includes an author$1 (Bs note about the real life Wright brothers and the true story of the first flight. Find out in this Level 1 I Can Read book complete with original illustrations from the creators of Pete the Cat, Kimberly and James Dean. Pete the Cat and the Wright Brothers is perfect for children learning to sound out words and sentences. Whether shared at home or in a classroom, the short sentences, familiar words, and simple concepts of Level One books support success for children eager to start reading on their own..s
new kids books 2024 fall.
Keywords: Pete, -- the Cat (Fictitious character) -- Juvenile fiction; Wright, Orville, -- 1871-1948 -- Juvenile fiction; Wright, Wilbur, -- 1867-1912 -- Juvenile fiction; Cats -- Juvenile fiction; Flight -- Juvenile fiction